2011
DOI: 10.1002/pmic.201000576
|View full text |Cite
|
Sign up to set email alerts
|

Simulating and validating proteomics data and search results

Abstract: The computational simulation of complete proteomic data sets and their utility to validate detection and interpretation algorithms, to aid in the design of experiments and to assess protein and peptide false discovery rates is presented. The simulation software has been developed for emulating data originating from data-dependent and data-independent LC-MS workflows. Data from all types of commonly used hybrid mass spectrometers can be simulated. The algorithms are based on empirically derived physicochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 59 publications
1
31
0
Order By: Relevance
“…Indeed, it has been estimated that at 25000 fwhm mass spectrometry resolution, around 35 and 20% of the EMRTs are composite in MS E and HDMS E , respectively. 43 Identification Transfer. Identification transfer is the process of assigning QR EMRTs with a sequence by pairing it with an IR peptide in order to retrieve quantitative measurement from QR.…”
Section: Algorithm Development and Applicationsmentioning
confidence: 99%
“…Indeed, it has been estimated that at 25000 fwhm mass spectrometry resolution, around 35 and 20% of the EMRTs are composite in MS E and HDMS E , respectively. 43 Identification Transfer. Identification transfer is the process of assigning QR EMRTs with a sequence by pairing it with an IR peptide in order to retrieve quantitative measurement from QR.…”
Section: Algorithm Development and Applicationsmentioning
confidence: 99%
“…The retention time constraint significantly decreases the number of interferences and mirrors experimental conditions of scheduled SRM measurements more closely. SSRCalc is used by several other SRM assay design and simulation programs (17,41), and we validate our use of SSRCalc in the supplementary discussion with a large data set and also discuss other predictors based on support vector machines (27). We showed that the effect of using retention time scheduling with a window size of 4 SSRCalc units (corresponding to roughly 2 min on a 30-min gradient) can be comparable with adding one more transition to an assay.…”
Section: Discussionmentioning
confidence: 87%
“…Multidimensional chromatography, when properly implemented, should have a positive impact on overall separation capacity [13,14]. Alternatively, an additional dimension of separation such as ion mobility (IM) can be very effective in reducing chimeric and composite interferences and the benefits of this approach have been demonstrated in dataindependent analysis (DIA) strategies [14,15]. The application and combination of IM with DDA is less common.…”
Section: Introductionmentioning
confidence: 99%